2022
DOI: 10.1111/jonm.13650
|View full text |Cite
|
Sign up to set email alerts
|

Organizational climate and interpersonal interactions among registered nurses in a neonatal intensive care unit: A qualitative study

Abstract: Aim The aim of this work is to describe the organizational climate and interpersonal interactions experienced by registered nurses in a level III neonatal intensive care unit. Background Neonatal nurses have a demanding task in caring for a varied, highly vulnerable patient population and supporting patients' families. Nurses' psychosocial work environment affects quality of care as well as nurses' job satisfaction and organizational commitment. Method Semistructured interviews with 13 nurses, covering numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…These results concur with this study as it was pointed out that there is a lack of trust among the parties. Furthermore, the results of this study concur with the results of the study conducted in Sweden by Bry and Wigert ( 2022 ). The study reported that senior nurses being the supervisors perceived that there was a generational shift in attitudes concerning the way they communicate with recently graduated nurses as they felt that new professional nurses could not tolerate being corrected and took things as personal (Bry & Wigert 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results concur with this study as it was pointed out that there is a lack of trust among the parties. Furthermore, the results of this study concur with the results of the study conducted in Sweden by Bry and Wigert ( 2022 ). The study reported that senior nurses being the supervisors perceived that there was a generational shift in attitudes concerning the way they communicate with recently graduated nurses as they felt that new professional nurses could not tolerate being corrected and took things as personal (Bry & Wigert 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the results of this study concur with the results of the study conducted in Sweden by Bry and Wigert ( 2022 ). The study reported that senior nurses being the supervisors perceived that there was a generational shift in attitudes concerning the way they communicate with recently graduated nurses as they felt that new professional nurses could not tolerate being corrected and took things as personal (Bry & Wigert 2022 ). There is no doubt that this reported disharmony between the two parties might affect negatively the new professional nurses’ professional growth as well as patient care if not properly handled.…”
Section: Discussionsupporting
confidence: 92%
“…Turnover intention is important to nurse managers as it reduces perceived patient‐centered care and aspects of care quality (Huang et al, 2021). Moreover, nurses' turnover increases managerial burdens, for example, to recruit and train new nurses (Bry & Wigert, 2022). The literature has examined various possible means of reducing turnover intention, including an improvement in working environment (Al‐Hamdan et al, 2017; Chang et al, 2019), enhancing affective commitment (Huyghebaert et al, 2019), enhancing emotional intelligence (Al‐Hamdan et al, 2020) and resilience (Yu et al, 2021), and enhancing job satisfaction (Gillet et al, 2018; Halcomb & Bird, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%